Effect of foliar nitrogen and sulfur on petit manseng (Vitis vinifera L.) grape composition. (3rd July 2017) - Kelly, Molly; Gill Giese, W.; Velasco-Cruz, Ciro; Lawson, Laura; Ma, Sihui; Wright, Melissa; Zoecklein, Bruce
ABSTRACT: Vineyard applications of foliar nitrogen (N) and sulfur were evaluated in the Yadkin Valley of North Carolina in 2011 and 2012 as a means to modify grape composition of Vitis vinifera cv. petit manseng. Four treatments were applied each year in a randomized complete block design with six replicates of six vines each: untreated control, soil N at 30 kg/ha, foliar N at 15 kg/ha and foliar N at 15 kg/ha plus sulfur at 5 kg/ha. Fruit ammonia and yeast assimilable nitrogen (YAN) concentrations increased in foliar-treated vines both seasons compared to control vines. Total glycosides (TGGs) increased ∼80% in foliar N/sulfur-treated vines compared to control vines in 2011, and TGGs increased ∼157% in foliar N/sulfur-treated vines relative to glycoside level in foliar N alone in 2012. Foliar N and foliar N/sulfur applications increased the majority of amino acid concentrations analyzed in 2011. Measured concentrations of various amino acids, partly responsible for aroma and flavor of petit manseng wines, were differentially dependent on the method of N application. Foliar applied nitrogen may be an effective technique to contribute to berry composition optimization of petit manseng grown in a warm, humid climate.